The interplay between microbiome and host factors in pathogenesis and therapy of head and neck cancer - Raudenská, Martina; Bugajová, Maria; Kalfeřt, David; Plzák, Jan; Šubrt, Adam; Tesařová, Petra; Masařík, Michal (Biochimica et biophysica acta, CR. Reviews on cancer, 2024)
Heterogeneous cancers that lack strong driver mutations with high penetrance, such as head and neck squamous cell carcinoma (HNSCC), present unique challenges to understanding their aetiology due to the complex interactions between genetics and environmental factors. The interplay between lifestyle factors (such as poor oral hygiene, smoking, or alcohol consumption), the oral and gut microbiome, and host genetics appears particularly important in the context of HNSCC. The complex interplay between the gut microbiota and cancer treatment outcomes has also received increasing attention in recent years. This review article describes the bidirectional communication between the host and the oral/gut microbiome, focusing on microbiome-derived metabolites and their impact on systemic immune responses and the modulation of the tumour microenvironment. In addition, we review the role of host lifestyle factors in shaping the composition of the oral/gut microbiota and its impact on cancer progression and therapy. Overall, this review highlights the rationality of considering the oral/gut microbiota as a critical determinant of cancer therapy outcomes and points to therapeutic opportunities offered by targeting the oral/gut microbiota in the management of HNSCC.
Keywords: Tumor Microenvironment; Head and Neck Neoplasms; Gastrointestinal Microbiome; nádorové mikroprostředí; Squamous Cell Carcinoma of Head and Neck; střevní mikroflóra; Humans; Life Style; životní styl; lidé; dlaždicobuněčné karcinomy hlavy a krku; nádory hlavy a krku